Localized Delivery of Cl-Amidine From Electrospun Polydioxanone Templates to Regulate Acute Neutrophil NETosis: A Preliminary Evaluation of the PAD4 Inhibitor for Tissue Engineering - Fetz, Allison E.; Neeli, Indira; Buddington, Karyl K.; Read, Robert W.; Smeltzer, Matthew P.; Radic, Marko Z.; Bowlin, Gary L. (Frontiers in Pharmacology, 2018)
Upon interaction, neutrophils can potentially release neutrophil extracellular traps on the surface of an implanted electrospun template, which may be a significant preconditioning event for implantable biomaterials of yet unknown consequences. In this study, we investigated the potential of polydioxanone templates as a delivery vehicle for Cl-amidine, an inhibitor of peptidyl arginase deiminase 4, and if drug elution could attenuate peptidyl arginase deiminase 4-mediated NETosis in the vicinity of implanted templates. Electrospun polydioxanone templates were fabricated with distinct architectures, small diameter (0.4 µm) or large diameter (1.8 µm) fibers, and incorporated with 0-5 mg/mL Cl-amidine to examine dose-dependent effects. Acute neutrophil-template interactions were evaluated in vitro with freshly isolated human neutrophils and in vivo with a rat subcutaneous implant model. The in vitro results suggest large diameter templates with 0 mg/mL Cl-amidine significantly attenuate NETosis compared to small diameter templates. As the drug concentration increased, NETosis was significantly decreased on small diameter templates in a dose-dependent manner. The opposite was observed for large diameter templates, indicating multiple mechanisms of NETosis may be regulating neutrophil template preconditioning. Similar results were observed in vivo, verifying local NETosis inhibition by Cl-amidine eluting templates in a physiological environment. Importantly, large diameter templates with Cl-amidine enhanced neutrophil invasion and survival, supporting the potential for long-term modulation of tissue integration and regeneration. This preliminary study demonstrates a novel delivery vehicle for Cl-amidine that can be used to regulate acute NETosis as the potential critical link between the innate immune response, inflammation, and template-guided tissue regeneration.